1386 Presenting injuries (farm and other) at a regional hospital in victoria, australia – linking prevention, promotion and place. (24th April 2018) - Brumby, Susan; Rahman, Muhammad Aziz; Zyl, Nic van; Vaughan, Vanessa
Abstract : Introduction: Over the last decade agriculture, forestry and fishing workers had the highest rate of workplace fatalities compared to other occupations in Australia. This is coupled with long distance to both health services and for ambulance assistance. To date, little work has been done on injury prevention at a regional place based level. This study examined the types and causes of farm injuries compared with other injuries presenting to a regional hospital based in an agricultural community in Western Victoria, Australia, with the aim of improving both prevention and care post injury. Methods: A retrospective study of database records was conducted on 41 429 patients attending the Accident and Emergency (A and E) Department of a regional hospital in Victoria during 2010–2015. Data were analysed using SPSS and EXCEL. Results: Most (91%) of the injuries were related to non-intentional harm accidents. The most common place of injury was the home (49%) and one in twelve (8%, n=3314) patients identified the place of injury as on-farm. The majority (83%) arrived by private car. The most common cause of on-farm injuries were: animals (24%), fall from a farm vehicle (11%), and materials (11%) such as nails, needlesticks, timber. Patients who were injured on-farm were more likely to be male compared to injuries from other places (75% vs 58%, p<0.001, RR 1.30, 95% CI: 1.26 to 1.35). Non-intentional harm was more commonly identified among people injured on-farm (99%) compared to other places (91%) (p<0.001, RR 1.08, 95% CI: 1.07 to 1.09). Patients injured on-farm were more likely to be categorised with higher triage (resuscitation, emergency and urgent) compared to injury at other places (33% vs 27%, p<0.001, RR 1.35, 95% CI: 1.20 to 1.53). Conclusion: This presentation will highlight the most common injuries occurring in a regional community and make recommendations on place-based health promotion/prevention strategies to address both farm and community injuries.